Body Rejuvenation - Alam, Murad; Pongprutthipan, Marisa; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
In recent years, there has been a growing emphasis on minimally invasive procedures, which have revolutionized the safety and convenience of cosmetic surgery. Such procedures are often performed in combination with a series of minor procedures collectively providing results formerly possible only after major incisional surgery. As patients and physicians have become familiar with minimally invasive facial rejuvenation, there is growing interest in adapting techniques for use off the face. The same lasers, fillers, and other techniques that can improve the appearance of the forehead or lips are useful for the chest or hands. Of course, procedures have to be modified for use on the trunk and extremities. For instance, off the face, gentler treatment approaches can be preferable, in part because of reduced blood perfusion and slower wound healing. Body Rejuvenation is the first practical manual that describes off-the-face minimally invasive rejuvenation. Sections are organized by body area, and within each section, individual chapters contain step-by-step treatment algorithms. Chapters are brief and concise by design, so interested readers can readily obtain the information necessary to treat patients successfully. Expert authors share their experience with body rejuvenation, so that you don t have to learn by trial and error.
Neck and Upper Chest -- Treatment of Platysmal Bands with Botulinum Toxin -- Treatment of Neck Laxity with Radiofrequency and Infrared Light -- Treatment of Neck Laxity with Therapeutic Ultrasound -- Treatment of Neck Fat with Injectable Adipolytic Therapy -- Treatment of Poikiloderma with Fractional Resurfacing -- Treatment of Poikiloderma with Chemical Peeling -- Treatment of Poikiloderma by Pigment and Vascular Lasers -- Back and Chest -- Treatment of Truncal Acne Scarring -- Truncal Hair Removal -- Revision of Disfiguring Surgical Scars of the Back -- Breast -- Breast Reduction Through Liposuction -- Botulinum Toxin A for Upper Thoracic Posture and the Appearance of a Breast Lift -- Hands (and Feet) -- Treatment of Keratoses and Lentigines with Peels and PDT -- Off-Face Laser Treatment of Keratoses and Lentigines -- Treatment of Hand Veins with Sclerotherapy -- Treatment of Hand Atrophy with Fat Transplantation -- Arms (and Legs) -- Reduction of Arm Fat by Liposuction -- Reduction of Excess Arm Skin via Surgical Excision -- Skin Tightening of the Arms and Legs with Radiofrequency and Broadband Light -- Sclerotherapy of Leg Veins -- Ambulatory Phlebectomy -- Endovenous Laser and Radiofrequency Treatment of Leg Veins -- Abdomen, Thighs, Hips, and Buttocks -- Noninvasive Body Rejuvenation -- Reduction of Cellulite with Subcision® -- Body Contouring with Tumescent Liposuction -- Skin Tightening Off the Face with Radiofrequency and Broadband Light -- Female Genital Surgery -- Reduction of Excess Abdominal Skin via Liposuction and Surgical Excision -- Advanced and General Topics -- Ablative Laser Resurfacing Off the Face -- Prepackaged Injectable Soft-Tissue Rejuvenation of the Hand and Other Nonfacial Areas -- Cosmeceuticals Off the Face -- Special Considerations in Asian Patients -- Treatment and Prevention of Dyspigmentation in Patients with Ethnic Skin.
Keywords: Medicine; Dermatology; Surgery; Medicine & Public Health; Dermatology; Plastic Surgery